Effect of Levetiracetam Monotherapy in Nonlesional Focal Childhood Epilepsy - Kanemura, Hideaki; Sano, Fumikazu; Ohyama, Tetsuo; Sugita, Kanji; Aihara, Masao (Neuropediatrics, 2018)
This article compares the efficacy and tolerability of carbamazepine (CBZ) and levetiracetam (LEV) when used as initial monotherapy in children with nonlesional focal epilepsy. Patients with nonlesional focal epilepsy were subdivided into two groups according to the initial monotherapy: a LEV group administered LEV at an initial dose of 5 mg/kg/day and a CBZ group. Seizure response, adverse events, medication dose, reasons for discontinuing medication, adherence, and random serum levels were recorded. The overall percentage of patients who failed initial treatment and reasons for each treatment failure were determined. Data were analyzed from 183 children who received CBZ monotherapy and 46 children who received LEV monotherapy for ≥12 months. Overall, 126 patients (68.9%) became seizure-free with CBZ, compared with 37 patients (80.4%) with LEV. Moreover, four patients in CBZ and four patients in LEV groups showed a >50% reduction in seizure frequency. The efficacy rate was significantly higher and the adverse event rate was significantly lower in the LEV group than in the CBZ group (p = 0.0129 and p = 0.0039, respectively). LEV may offer superior efficacy and a lower risk of adverse effects compared with CBZ. LEV as initial monotherapy may represent a valuable treatment option for children with nonlesional focal childhood epilepsy.
Keywords: levetiracetam (LEV); epilepsy; antiepileptic drug (AED); initial monotherapy; child